Translation Studies Research Development in Indonesia - Haru Deliana Dewi (Humaniora, 2019)
This paper is an overview on the development of Translation Studies (TS) research in Indonesia from 2008 to 2018. The study aims to discover whether the TS research conducted by the students of ten Indonesian universities has followed the present trends of TS research in the world. The data were obtained from the final papers (undergraduate theses, Master’s degree theses, and doctoral theses) of the universities having translation programs in Indonesia, particularly on Java and Bali Islands. The titles of the final papers were analyzed to obtain a general idea of what topics of TS research are usually investigated by Indonesian university students. The results show that most of the topics are categorized into text analysis and translation (product-oriented research), and very few belong to the process-oriented research, participant-oriented research, and other themes. This leads to the conclusion that TS research in Indonesia has not yet developed well and has not varied according to the international TS research progress.